Characterization of the levan produced by Paenibacillus bovis sp. nov BD3526 and its immunological activity. (25th June 2016) - Xu, Xiaofen; Gao, Caixia; Liu, Zhenmin; Wu, Jiang; Han, Jin; Yan, Minghui; Wu, Zhengjun
Highlights: Paenibacillus bovis sp. nov BD3526 produced about 36.25 g/L levan in a semi-defined medium. The peak molecular weight of the levan is exceeding 2.6 × 106 Da. The levansucrase was identified as 87 kDa by SDS-PAGE and in situ levan synthesis. The levan significantly stimulated the proliferation of spleen cells in vitro. The levan could up-regulate the expression of TNF-α in spleen cells in vitro . Abstract: Paenibacillus bovis sp. nov BD3526 synthesizes a large amount of exopolysaccharides (EPSs) (36.25 g/L) in a semi-defined chemical medium containing 20% (w/v) sucrose. The EPSs were extracted from the cultured broth by ethanol precipitation and purified via anion-exchange and gel permeation chromatography. The Fourier transform infrared (FT-IR) and nuclear magnetic resonance (NMR) spectra showed that the primary EPS fraction (F1) was a linear β (2 → 6)-linked levan. The peak molecular weight ( M p ) of the levan exceeded 2.6 × 10 6  Da based on high-performance size-exclusion chromatography (HPSEC). The levan adopted a spherical conformation in aqueous solution as confirmed by transmission electron microscopy (TEM). The corresponding levansucrase was identified by SDS-PAGE analysis and in situ polymer synthesis. The in vitro assay demonstrated that the levan significantly stimulated the proliferation of spleen cells and induced the expression of TNF-α, indicating its potential as a natural immunomodulator.